Determination of Mineral Elements in Fifteen Medicinal Herbs and Their Infusions by Inductively Coupled Plasma Atomic Emission Spectrometry - Yan, Qinghua; Yang, Li; Zhang, Huirong; Niu, Liyuan (Asian Journal of Chemistry, 2011)
Nine mineral elements (Na, K, Ca, Mg, Cu, Zn, Mn, Se, Al) were determined in 15 medicinal herbs and their infusions consumed for people's daily lives and medicinal purposes in China. Microwave digestion procedure was applied under optimized conditions for dissolution of medicinal herbs. The concentrations of these mineral elements in the medicinal herbs and their infusions were determined by inductively coupled plasma emission spectrometry. The correlation coefficients (r) for all the analysis elements were showed in 0.9990-0.9999. The standard addition method was considered as a validation method of the accuracy and precision. Results showed the mineral and trace element content of medicinal herbs and their infusions displayed a wide variability, distribution of the elements in the medicinal herbs and their infusions was high for K, Na, Ca and Mg. However, some trace element concentrations in infusions were not high and they were very low or nil especially for Al, Cu, Mn and Se. The recovery of the element was 97- 105 % and the RSD < 5.0 %. It is concluded that the present techniques are suitable for the routine determination of mineral elements concentration in medicinal herbs and their infusions. This study is to give important reference value to people due to individual differences by adjusting the herbal tea to complement the different trace elements.